THE EFFECT OF TIKTOK LIVE HOST INTERACTION, VIEWING INTENSITY, AND PROMOTION ON IMPULSE PURCHASES OF SKINTIFIC PRODUCTS ON TIKTOK SHOP - Khurrotul Lutfiyah; Rendy Adi Saputra; Mochamad Rizal Yulianto; Alshaf Pebrianggara; Bayu Hari Prasojo (Antis Publisher, 2026)
Objective: The purpose of this study is to demonstrate that host interaction, viewing intensity, and promotions influence impulsive purchases of Skintific products on TikTok Shop. Method: This study employs a quantitative approach, with data collected via a questionnaire. The data analysis method used is Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Results: The results indicate that host interaction, viewing intensity, and promotions positively and significantly influence impulsive purchasing. This suggests that stronger host communication, more frequent viewing exposure, and more attractive promotions increase the likelihood of consumers making spontaneous purchases. Novelty: Therefore, optimizing live-streaming interaction, audience engagement, and real-time promotional strategies can be prioritized to improve impulsive sales performance.